Determinants of formula feeding among mothers with infants and young children in six Sub Sahara African countries: Multilevel analysis of data from demographic and health survey. - Mohammed Seid Ali; Alebachew Ferede Zegeye; Belayneh Shetie Workneh; Gebreeyesus Abera Zeleke; Enyew Getaneh Mekonen; Agazhe Aemro; Berhan Tekeba; Tadesse Tarik Tamir; Mulugeta Wassie; Bewuketu Terefe (PLoS ONE)
Introduction Formula feeding is providing infants with prepared formula as an alternative to or alongside breastfeeding. While breast milk is widely regarded as the optimal source of nutrition for infants, formula feeding is a common practice. The recommended approach is exclusive breastfeeding for the first six months, followed by the introduction of complementary foods after that period, which is crucial for child growth and development. Formal feeding has a negative impact on an infant's health, causing malnutrition and other illnesses. Therefore, this study was investigated to assess formula feeding and determinant factors among mothers with infants in six sub-Saharan African countries. Methods A total weighted sample of 26,119 mothers with infants and young children less than two years was included in this study. The data were taken from a recent demographic and health survey in six sub-Sahara African countries. A multilevel, multivariable logistic regression model was used to identify the determinant factors associated with formula feeding. In the multivariable analysis, the adjusted odds ratio with a 95% CI was used to declare a statistically significant association with formula feeding among mothers with infants. Results In this study, the proportion of mothers with infants who use formula feeding was 17.1%. In multilevel logistic analysis (model III), the significant factors associated with formula feeding were the age of the mothers; 25-34 years (AOR = 1.3; 95% CI (1.2-1.41)), 35-49 years (AOR = 1.4; 95% CI (1.22-1.54)), multiple children (AOR = 1.4; 95% CI (1.23-1.77)), maternal educational status; secondary and higher (AOR = 2.4; 95% CI (2.11-2.66)), mother's employment status; (AOR = 1.24; 95% CI (1.14-1.5));, richer households (AOR = 1.2; 95% CI (1.10-1.36)), place of delivery (AOR = 2.1; 95% CI (1.83-2.44)), household media exposure (AOR = 1.5; 95% CI (1.3-1.68))place of residence (AOR = 1.97; 95% CI (1.79-2.17)), community illiteracy level (AOR = 1.17; 95% CI (1.02-1.34)), and community media exposure (AOR = 1.2; 95% CI (1.03-1.38)). Conclusion Formula feeding among mothers with infants in Sub-Saharan Africa has emerged as a public health concern. The recommended approach is to promote exclusive breastfeeding for the first six months, followed by the introduction of complementary feeding after that period. Factors associated with formula feeding include older maternal age, secondary and higher education, delivery in health institutions, employment status, higher household income, twin births, urban residence, low community illiteracy rates, and increased community media exposure. Stakeholders and health policymakers should be focused on strategies to improve breast feeding and discourage infant formula feeding.